Trust and governance - Braithwaite, V. A. (Valerie A.), 1951-; Levi, Margaret (New York : Russell Sage Foundation, 1998)
Trust and Governance asks several important questions: Is trust really essential to good governance, or are strong laws more important? What leads people either to trust or to distrust government, and what makes officials decide to be trustworthy? Can too much trust render the public vulnerable to government corruption, and if so what safeguards are necessary? In approaching these questions, the contributors draw upon an abundance of resources to offer different perspectives on the role of trust in government. Enriched by perspectives from political science, sociology, psychology, economics, history, and philosophy, Trust and Governance opens a new dialogue on the role of trust in the vital relationship between citizenry and government.
Chapter 10: Uncertainty, Appraisal, and Common Interest: The Roots of Constituent Trust // William T. BiancoPart IV: Trust Responsiveness; Chapter 11: Trust and Democratic Governance // Tom R. Tyler; Chapter 12: Republican Theory and Political Trust // Philip Pettit; Chapter 13: Trusting Disadvantaged Citizens // Mark Peel; Chapter 14: Institutionalizing Distrust, Enculturating Trust // John Braithwaite; Conclusion // Valerie Braithwaite and Margaret Levi; Index
Includes bibliographical references and index.
JSTOR
Keywords: Political ethics; Political sociology; Democracy; Democracy; Morale politique; Sociologie politique; Démocratie.; democracy; SOCIAL SCIENCE -- General; Democracy; Political ethics; Political sociology; Demokratie; Politische Ethik; Politische Soziologie; Regierung; Vertrauen; Aufsatzsammlung; Politieke ethiek; Democratie; Politiek vertrouwen; Démocratie.; Morale politique; Sociologie politique; Confiance -- Aspect politique; Aufsatzsammlung